Implementasi Tata Kelola Teknologi Informasi Perpustakaan (Studi Kasus : Universitas Islam Negeri Raden Fatah Palembang) - Nopriani, Fathiyah (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
The Raden Fatah State Islamic University Library in Palembang is one of the university facilities that supports learning and teaching for students and lecturers. Performance at the Raden Fatah State Islamic University library in Palembang provides the best service for the entire academic community of the university by using the Library Information System, namely SLiMS (Senayan Library Management System). During the use of SLiMS, there was no evaluation using the COBIT 5 framework. The analysis was obtained from the results of the respondents' answers, namely the SLiMS manager with several domains from COBIT 5.